PERUBAHAN MATA PENCAHARIAN MASYARAKAT PASCA PENGEMBANGAN JALAN ALAI-BY PASS (Studi Kasus: Kelurahan Lubuk Lintah Kecamatan Kuranji Kota Padang) - Febriani, Febriani; Prahara, Surya; Elfemi, Nilda (Pendidikan Sosiologi, 2014)
This research of background by existence of policy of government for the development of road, street of Alai-By Pass, where one of them as main road and gand alternative avacuate so that facilitating society to save self. This matter bring impact to change of society living residing in sub-district of deep hollow leech. This research aim to for the knowing of society living before and after development of road. Street of Alai-By Pass in sub- district of deep hollow leech disrtrict of Kuranji and of knowing mount earnings of society in sub-district of deep hollow leech district of Kuranji town field. Â Theory of used is change of social according to this Neil Smelser research use approach of research qualitative with descriptive type. Informan at this reseach is original society who live in frontage walke Alai- By Pass and elite figure and also officer of subdistrict of deep hollow leech. Election of informan at this research use technique of purposive sampling. Data type the used is primary data and data of sekunder. Method data collecting conducted in three way of. (1) observation (observation non-participant), (2) cir cumstantial interview, (3) documentation study. Its analysis data used with model analysis data of interaktif (Miles and of Huberman) including in four step, that is: (1) data collecting phase, (2) phase reduce data, (3) phase presentation of data and (4) conclusion phase.